Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Given: f(1) = 3x– 7, 9(x) = 2x^2 – 3x +1, h(x) = 4x + 1, k(x) = –x^2+3
Find: (h o g) (x)


Sagot :

Answer:

(h o g) (x) = h(g(x))

Step-by-step explanation:

(h o g) (x) = h(g(x)) = 4(g(x))+1 = 4(2x^2 -3x + 1 ) + 1

= 4*2x^2 - 4*3x + 4*1 + 1

= 8x^2 - 12x + 4 + 1

= 8x^2 - 12x + 5